Kültürel Bellek Olarak Necati Cumalı’nın Viran Dağlar Romanında Balkanlar (4th International Balkan Studies Congress Proceedings, 2025)
Necati Cumalı (1921-2001), who was born in Şorina, located in the Western Macedonia region today, as the child of a family that emigrated from the Balkans, produced works in literary genres such as poetry, stories, novels and theater. He is one of the important names of Turkish literature. The Balkans have a special place in his life and works. He tries to reveal his past roots and cultural memory together with this geography through his works. Because his roots are based here, his family lived in this geography for centuries, and he also spent his childhood and youth in the Balkans. Therefore, the Balkans occupy an important place in the construction of cultural memory and memory in his works. History, geography and geographical regions can also be mentioned in literary texts such as novels and stories based on the principle of narration. Because, in general terms, for the author who creates the text, the starting point of fiction or creating a nominal world is the outside world. Observations of the place that seems to be conveyed by the author as real, are trans-formed into a different form by being kneaded in the world of imagination. What is told here is sometimes based on history, sometimes on memories experienced by people in the past, and sometimes on legendary narratives. Viran Dağlar is an important symbol of the region where Cumalı spent his childhood. This novel also occupies an important place in the author’s literary geography. The unique structure of Macedonia at that time, village and rural life is presented in a fiction with all its aspects and with a lively narrative. The period in which the novel is set is a very ac-tive and complex period in terms of political events in the Balkan geography. II. The uneasiness of the people in the region after the Constitutional Monarchy and just be-fore the Balkan Wars, their thoughts of migrating to Anatolia, and the anxious waits in cities and towns are beautifully reflected. Zülfikar Bey in the novel Viran Dağlar can also be seen as a symbol of the efforts to keep the Ottoman Empire alive in the Balkans. In this study, the novel Viran Dağlar by Necati Cumalı, who was born in the Balkans, spent his childhood and youth there, and then had to migrate to Anatolia, will be examined with a biographical reading method. It will be tried to reveal how the cultural memory of a person/writer is constructed through the Viran Dağlar.